The Rhetorics of Labour Contracting As a Managerial Tool among Oil Multinational Corporations (Mncs) In Nigeria - Ajonbadi, Hakeem Adeniyi (Archives of Business Research, 2016)
This paper attempts to investigate how labour contracting is employed as a managerial tool by the oil multinational corporations (MNCs) in Nigeria. In recent years, there have been agitations by trade unions who have fiercely resisted the proliferation of contract workers in the oil industry. Violations of trade union rights are widespread in Nigeria and include the intimidation of workers; refusal by employers to recognise trade unions; and the dismissal of workers’ representatives for trade union activities. At the same time, there have been concerted efforts on the part of the management of the oil multinationals and the government to arrest the situation. However, till date, few studies have categorically examined how labour contracting could be used as a managerial instrument as purportedly claimed by the affected workers and the trade unions. This research report was designed to explore the experiences of the contract workers, especially when juxtaposed with their colleagues on permanent employment. Using a qualitative research method, and employing survey and interview, the findings show strong resentment on the part of contract workers who lamented poor motivation, job dissatisfaction, poor career prospect, almost non-existing training, and poor working relations with their colleagues on the other divide of the employment ladder. Keywords: Contract staff, Employment relations, Flexibility, Labour contracting, Multinational corporations.